Hypothesis: cytokines may be activated to cause depressive illness and chronic fatigue syndrome. - Ur, E; White, P; Grossman, A (1992)
Abnormalities in the regulation of the hypothalamo-pituitary-adrenal (HPA) axis are a well recognised feature of endogenous depression. The mechanism underlying this phenomenon remains obscure although there is strong evidence suggesting excessive CRH activity at the level of the hypothalamus. We propose a novel hypothesis in which we suggest that the aetiological antecent to CRH hyperactivity is cytokine activation in the brain. It is now well established both that interleukins -1 and -6 are produced in a number of central loci and that cytokines are potent stimulators of the HPA axis. Hence, we suggest that activation of IL-1 and IL-6 by specific mechanisms (such as neurotropic viral infection) in combination with the consequent CRH-41 stimulation, may (via their known biological effects) underly many of the features found in major depression and other related disorders, particularly where chronic fatigue is a prominent part of the symptom complex. This theory has considerable heuristic value and suggests a number of experimental stratagems which may employed in order to confirm or reject it.